180°- versus 360°-Rotation bei der SPECT des Skeletts - Reuland, P.; MüllerSchauenburg, W.; Kühn, H.; Keller, K. D.; Feine, U. (Nuklearmedizin - NuclearMedicine, 1988)
Opinions differ as to the advantages of the 180° and the 360° techniques concerning myocardial scintigraphy with 201TI. Following our own encouraging experiences with the 180° technique, we have looked for cases in bone scintigraphy where reconstructions from a semicircle could be advantageous over a full circle reconstruction. There were metastases and foci of osteomyelitis in spine, ribs and skull (especially in the skull base), to be seen better in reconstructions using images out of 180° close to the object. In knee SPECT a closer radius of rotation can be chosen with single-head cameras so that, when using the 180° technique, a better reproduction of the anatomical structures and pathological alterations is achieved.